New model for confinement of reinforced concrete columns with an ultra-high strength close to 200 MPa. (15th November 2019) - Abdesselam, Halima; Kassoul, Amar; Bouzid, Haytham
Highlights: Assembled database of 300 experimental results of confined concrete with transverse steel. Performance of 20 existing peak strength concrete and corresponding axial strain models. Development of a new confinement model considers the ultra-high strength of concrete up to 200 MPa. The predicted model gives a good trend and a better accurate for active confinement close to 200 MPa. Abstract: The objective of this work is to develop a new confinement model for ultra-high strength concrete columns confined by transverse reinforcement. First, the mechanism of confinement with transverse reinforcement of square and rectangular section columns has been described. In this context, the existing peak strength and corresponding strain of the stress-strain models, with normal strength (NSC) and high strength (HSC) are selected. Next, the assembled database covering 300 existing experimental data in the literature with an unconfined compressive strength ranging between 20 MPa and 200 MPa is exposed. In order to evaluate the performance of the existing confinement models, three statistical indicators were used, namely: the coefficient of determination (R 2 ), root mean square error (RMSE) and standard deviation (SD). Afterward, the performance of 20 existing confinement models was implemented. According to this study, the proposed peak strength concrete and the corresponding axial strain showed a good performance compared with the 20 selected models. In addition, the expressions of the proposed models are simple and easy to use for design applications.